Biohydrogen Production via Dark Fermentation with Pig Manure and Glucose Using pH‐Dependent Feeding. Issue 8 (27th May 2020) - Weide, Tobias; Hernández Regalado, Roberto Eloy; Brügging, Elmar; Wichern, Marc; Wetter, Christof
Abstract: Process controls for mesophilic dark fermentation using a pH‐dependent feeding strategy without NaOH addition were examined. One reactor utilizing microorganism holdback and two continuously stirred‐tank reactors (CSTRs) with the same volume were employed. These were fed with pig manure and glucose as cosubstrates. Different hydraulic retention times were applied. The target pH was 5.5 within a limited range and controlled by varying organic loading rate. When the pH target interval was exceeded, the hydrogen production rate ( HPR ) decreased, and CH4 was produced. A pH below the target interval had positive effects on the HPR . Abstract : Dark fermentation was performed on a semi‐technical scale without NaOH addition, and the pH was maintained only by adjusting the organic loading rate depending on the pH. Possible applications of pig manure for dark fermentation were also investigated, leading to new findings which contribute to the implementation of large‐scale biohydrogen production from biomass.